2019
DOI: 10.3389/fpsyg.2019.02742
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Events, Personality and Psychopathology in Takotsubo Syndrome: A Systematic Review

Abstract: Objective: Takotsubo syndrome (TTS) is a transient heart disease that has been historically related to the occurrence of psychological (emotional) factors ("broken heart" syndrome). We aimed to conduct a systematic review analyzing the role of psychological factors in TTS. Methods: All studies on TTS and psychological factors from January 1991 through April 2019 were scrutinized according to the Cochrane Collaboration and the PRISMA statements. Selected studies were additionally evaluated for the Risk of Bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Our results regarding personality traits in TTS patients are part of an open debate, since there are only a few conflicting studies of TTS, as opposed to other cardiac diagnoses, such as ACS [11]. Thus, further studies are needed in order to understand if and how personality traits are related to TTS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our results regarding personality traits in TTS patients are part of an open debate, since there are only a few conflicting studies of TTS, as opposed to other cardiac diagnoses, such as ACS [11]. Thus, further studies are needed in order to understand if and how personality traits are related to TTS.…”
Section: Discussionmentioning
confidence: 89%
“…The role of emotional stressors as frequent triggers for TTS and the sometimes-observed comorbidity with different psychopathologic disorders have been largely discussed in the recent consensus document on the diagnostic workup and management of TTS [8]. However, evidence on the role and the incidence of psychological factors in TTS are sparse, and do not lead to any definitive assumption [11]. Although less frequent, the role of psychological factors as possible contributors to the evolution of cardiac events seems not to be specific to TTS, since it has also been observed in other cardiac diseases, including ACS [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this evidence should be translated into clinical practice to promote an integrated approach, especially in taking care of a patient with cardiovascular disease. If it is true that traumas, as well as other psychological and behavioral factors [ 60 ], can be considered risk factors for the onset of the same, it is also true that they may have an important weight in determining the outcome of the rehabilitation process, outlining the involvement of clinical psychologists in a multidisciplinary team that is able to treat the patient as a whole [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent and ever-growing corpus of evidence has shown that both specific personality traits (especially, the dimensions of Neuroticism and [low] Conscientiousness included in the Five-Factor Model; for an overview see Korotkov and Hannah, 2004 ; Dammeyer and Zettler, 2018 ) and personality disorders—defined as enduring maladaptive patterns of behavior, cognition, and inner experience—co-occur with various medical conditions, such as cardiovascular diseases, cancer, chronic pain, headaches, psoriasis, and other skin disorder, etc. (e.g., Rubino et al, 1995 ; Galli et al, 2011 , 2017 , 2019a , b ; Levine et al, 2021 ). Moreover, research has indicated that dysfunctional personality patterns negatively affect the clinical prognosis, increasing the risk of poor health outcomes (e.g., Johansen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%